The Correlation Between Student’s Vocabulary Mastery and Self-Efficacy to Speaking Performances (A Study at MA As-Salam, Geringging Baru, Riau) - Putri, Dinda Rahmadhani; Syafri, Frimadhona; Shakiyya, Zulfa (Sharia Economics Department Universitas KH. Abdul Chalim, Mojokerto, 2024)
This research aims to determine the correlation between self-efficacy and students' speaking performance. This research will use a correlational research model which is a quantitative research method. The location of this research is MA As-Salam which is located at JL. Budi Utomo No. 08, Sri Mekar Hamlet, District. Sentajo Raya, Riau. Research will be carried out after the thesis proposal is approved. In this research, the population is MA As-Salam students located in Geringging Baru, Kuantan Singingi, Riau. In this research, a random sampling technique was used. This research used two instruments. Namely tests and questionnaires. In this study, tests will be used to collect data about students' English Fluency. The results of this test will describe the student's English fluency. In general, instruments are classified based on tests, questionnaires, interviews, recordings, and many more. In this research, a questionnaire will be used as the instrument. Data for this research was collected from questionnaires and tests. This data was then analyzed to determine whether students' self-efficacy and vocabulary mastery influenced their English speaking performance based on their responses in the questionnaire and their performance in front of the class. A descriptive analysis of the questionnaire was carried out to determine the frequency distribution of each item. This is calculated using a mathematical formula. The results of this research show that the vocabulary proficiency of MA As-Salam Riau students is considered relatively low. The level of self-efficacy of MA As-Salam Riau students is in the moderate self-efficacy range. Correlation between Vocabulary Mastery and Speaking Performance It can be concluded that students with high vocabulary mastery tend to show commendable speaking performance. Correlation between Student Self-Efficacy and Speaking Performance. It can be concluded that higher levels of self-efficacy among students correlate with higher scores in speaking ability.